2023
DOI: 10.3390/nu15173832
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Health Behaviours, Attitudes and Beliefs of Women and Men during the Preconception and Interconception Periods: A Cross-Sectional Study of Adults on the Island of Ireland

Emma H. Cassinelli,
Abby McClure,
Ben Cairns
et al.

Abstract: Preconception health is increasingly seen as a key target for improving population health in the UK and Ireland, yet little is known about the attitudes and beliefs of adults regarding preconception care strategies. This online cross-sectional survey aimed to explore the health behaviours, attitudes and beliefs of adults of reproductive age in regard to preconception health and care. The survey was developed by reviewing the previous literature and engaging with those from the target group. It is one of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…While preconception health recommendations extend to all individuals of reproductive age, it is noteworthy that the bulk of interventions and messaging predominantly concentrate on women (Robbins et al, 2016 ; Thompson et al, 2017 ; Mello et al, 2020 ), Such an emphasis may inadvertently reinforce prevailing societal beliefs that women bear the primary responsibility for safeguarding children’s health (Mello et al, 2019 , 2020 ; McGowan et al, 2020 ). In a study that explored the health behaviors, attitudes, and beliefs of adults of reproductive age in regard to preconception health in Irland, the predominant view among participants highlighted the significance of preconception care, with a stronger inclination towards the necessity for women, as opposed to men, to adopt health-promoting behaviors prior to conception (Cassinelli et al, 2023 ). Studies conducted with male participants in the United Kingdom, and the United States, have indicated a common perception among men that their opinions are often overlooked in matters of reproductive health, leading to a predominant focus on women in such discussions (Hamm et al, 2019 ; Grace et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While preconception health recommendations extend to all individuals of reproductive age, it is noteworthy that the bulk of interventions and messaging predominantly concentrate on women (Robbins et al, 2016 ; Thompson et al, 2017 ; Mello et al, 2020 ), Such an emphasis may inadvertently reinforce prevailing societal beliefs that women bear the primary responsibility for safeguarding children’s health (Mello et al, 2019 , 2020 ; McGowan et al, 2020 ). In a study that explored the health behaviors, attitudes, and beliefs of adults of reproductive age in regard to preconception health in Irland, the predominant view among participants highlighted the significance of preconception care, with a stronger inclination towards the necessity for women, as opposed to men, to adopt health-promoting behaviors prior to conception (Cassinelli et al, 2023 ). Studies conducted with male participants in the United Kingdom, and the United States, have indicated a common perception among men that their opinions are often overlooked in matters of reproductive health, leading to a predominant focus on women in such discussions (Hamm et al, 2019 ; Grace et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted with male participants in the United Kingdom, and the United States, have indicated a common perception among men that their opinions are often overlooked in matters of reproductive health, leading to a predominant focus on women in such discussions (Hamm et al, 2019 ; Grace et al, 2019 ). However, researchers are stressing upon the significance of extending preconception care to men as several studies have highlighted the influence of paternal health factors, including obesity, cardiovascular health, and work conditions, on birth outcomes (Davey Smith et al, 2007 ; Hillman et al, 2013 ; Cassinelli et al, 2023 ). A recently published systematic review showed that primary care-based preconception interventions are effective in improving health knowledge and reducing preconception risk factors in women, with limited evidence for their effectiveness in men indicating a need for further research in this area.…”
Section: Introductionmentioning
confidence: 99%